2022
DOI: 10.1097/j.jcrs.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Long term efficacy and safety profiles of iris-fixated foldable anterior chamber phakic intraocular lens implantation in eyes with ≥ 10-year follow-up

Abstract: To evaluate the long-term efficacy, safety, predictability, and stability of a foldable anterior chamber phakic intraocular lens (pIOL) (Artiflex) implantation in eyes with more than 10 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 17 publications
8
17
0
Order By: Relevance
“…Finally, corneal endothelial cell changes were also evaluated, with an ECD loss of 2.01% at 4 weeks after surgery that increased to 9.11% at the end of the follow-up (13 years). This ECD loss is consistent with those reported in other long-term series evaluating the performance of the same pIOL [1,2]. Papa-Vetorazzi et al [2] found in a sample of eyes implanted with the Arti ex pIOL and followed for more than 10 years a mean ECD loss of 12.2 ± 12.5%.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Finally, corneal endothelial cell changes were also evaluated, with an ECD loss of 2.01% at 4 weeks after surgery that increased to 9.11% at the end of the follow-up (13 years). This ECD loss is consistent with those reported in other long-term series evaluating the performance of the same pIOL [1,2]. Papa-Vetorazzi et al [2] found in a sample of eyes implanted with the Arti ex pIOL and followed for more than 10 years a mean ECD loss of 12.2 ± 12.5%.…”
Section: Discussionsupporting
confidence: 88%
“…Concerning IOP, there was a non-signi cant trend to its increase in the initial postoperative period (4 weeks postoperatively), and a signi cant reduction afterwards from the 4-week to 1-year postoperative visit. Similarly, no signi cant increases in IOP have been also reported in other long-term series evaluating the outcomes of the Arti ex pIOL [1,2]. This is consistent with the maintenance of a wide anterior chamber after surgery and a minimal reduction of ACD.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our series, the percentage of eyes that lost more than 1.6% of EC density yearly (upper limit of normality obtained from the study by Bourne et al) was 19.7% (15/76). 1 However, of those 15 eyes, 11 had an endothelial cell count (ECC) of more than 2000 cells/mm 2 and none have lost more than 25% of their EC density at the final follow-up. Four eyes of 3 patients (5.2%) had less than 2000 cells/mm 2 and have lost more than 25% of their ECC at the final followup, and this is similar to the 5-year results reported by Jonker et al in their Artiflex study (4.3% -4.4%).…”
mentioning
confidence: 99%